“Characterization and Reduction of dissolved and colloidal matter in the manu-facture of recycled paper and cardboard in the company Inpetfa sac” - Elías Silupo, Jorge Wilmer (2020)
The use of recovery paper and cardboard as a raw material for the manufacture of recycled paper and cardboard, presents numerous environmental and economic advantages. However, it also has serious drawbacks due to the amount of contaminants that are introduced into the system. Contaminants that are in the form of dissolved and colloidal matter cannot be eliminated by conventional mechanical processes and when destabilized, by a sudden change in the conditions of the system, are directly responsible for the formation of spots and holes in the final product. The objective of the present work is to develop a procedure to determine the presence of dissolved and colloidal matter in the water of the paper process, in a practical and precise way. The waters characterized, are destabilized with a cationic polymer, favoring the formation of deposit designed for such purpose, which allows to carry out the quantitative determination by means of a chemical physical analysis system. With the developed method, once validated and its reproductivity determined, a study is carried out with recycled water obtained from pulp suspensions that contain the contaminants of the paper recycling process, such as adhesives, waxes, de-inking soaps, etc. The effect of different variables, such as the nature of the contaminant, the presence of deinking additives, the nature of the destabilizing agent and the characteristics of the medium (Ph, Temperature, Total Solids, DQO, DBO5, Oils and Fats etc) are studied. .); Likewise, a study of the waters of the process is carried out, with dissolved and colloidal matter contained in samples of different types of raw material: mixed paper, newspaper and recycled cardboard, obtaining the results after the chemical Physical treatment on average.  (Ph = 8.4, Temperature = 26.5 ° C, Total Solids = 150.26 mg / L, DQO = 750.82 mg / L, DBO5 = 300.24 mg / L, Oils and Fats = 48.56 mg / L etc.); in the manufacture of plates of agglomerated fibers in the company Inpetfa sac.